2021
DOI: 10.3390/toxics9020038
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin Inhibits Reactive Oxygen Species Generation via Akt/NF-κB/MAPK Signaling Pathways in Particulate Matter-Exposed Human Bronchial Epithelial Cells

Abstract: Background: Eupatilin is an active flavon extracted from the Artemisia species and has properties such as antioxidant, anti-inflammatory, and anti-cancer. We examined the effect of eupatilin using fine particulate matter (FPM) and human bronchial epithelial cell line (BEAS-2B) to confirm the potential of eupatilin as a therapeutic agent for respiratory diseases caused by FPM. Methods: Reactive oxygen species (ROS) levels were checked by flow cytometry to identify if FPM and eupatilin affect ROS production. Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition, Eupatilin may also play a role in other pathways, such as PI3K/AKT, NF-κB, MAPK and Nrf2 pathways. 24,61 Thus, whether these pathways also play a role in regulating inflammation and coagulation in sepsis needs further investigation. According to one study, Eupatilin can lower the expression of inflammatory mediators by inhibiting the NF-κB signaling pathway in endotoxin-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Eupatilin may also play a role in other pathways, such as PI3K/AKT, NF-κB, MAPK and Nrf2 pathways. 24,61 Thus, whether these pathways also play a role in regulating inflammation and coagulation in sepsis needs further investigation. According to one study, Eupatilin can lower the expression of inflammatory mediators by inhibiting the NF-κB signaling pathway in endotoxin-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are generated by various endotoxins (e.g., PM10 and LPS) to activate downstream signaling pathways in order to regulate the inflammatory response. Several studies have demonstrated that PM can trigger several signaling pathways to regulate PM10-induced inflammatory responses, including the AKT, ERK, JNK, and NF-κB signaling pathways [ 14 , 41 ]. The PI3K/AKT signaling pathway is known to play an important role in cell inflammation, apoptosis, angiogenesis, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…PM10 (PM with an aerodynamic diameter of under 10 μm) can easily be inhaled and deposited throughout the airways, which harms the human respiratory and circulatory systems [ 12 , 13 ]. As it is mainly absorbed through respiration, many studies related to pulmonary inflammation have been conducted, while reactive oxygen species (ROS)-mediated redox responsive signaling pathways, including phosphoinositide 3-kinase (P13K)/AKT, mitogen-activated protein kinase (MAPK), and nuclear κappa B (NF-κB), have been identified as major mechanisms of action explaining its toxicity [ 14 , 15 , 16 ]. In addition, PM10-induced pulmonary oxidative stress is associated with the release of various cytokines, such as inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1 beta (IL-1β), which can promote lung damage [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…PM exposure reduced transepithelial electrical resistance and the expression of tight junction proteins in human nasal epithelial cells [25][26][27]. Furthermore, PM exposure resulted in reactive oxygen species (ROS) production in cells, while pretreatment with an antioxidant (N-acetylcysteine) restored tight junction protein expression [25,28,29]. Diesel exhaust particles, a type of PM, induced the epithelial-to-mesenchymal transition (EMT), which is a process involving the loss of epithelial polarity and junctional proteins, in the sinonasal mucosa [30].…”
Section: Pathogenic Processes Of Chronic Rhinosinusitis Caused By Par...mentioning
confidence: 99%